Computational methods for electron transport and their application in nanodevices - Rungger, Ivan (Trinity College (Dublin, Ireland). School of Physics, 2009)
The present thesis deals with the development of theoretical and computational tools for the first principles study of ground state and electronic transport properties of nanoscale devices and the application of these tools to systems of current interest. The ground state properties are studied within density functional theory (DFT) using the SIESTA code, whereas the transport properties are investigated using the nonequilibrium Green's functions (NEGF) formalism implemented in the SMEAGOL code. This is itself is based on SIESTA. We present our implementation a new algorithm for the calculation of the self-energies for quasi one-dimensional systems. The main advantage of this method is that all the singularities in the computation are avoided wherever possible, .so that it is very stable and accurate. We also present a formalism for the inclusion of bound states in the calculation of the non-equilibrium charge density within the NEGF method, which we also use to treat systems with very weakly coupled states. Based on this formalism an adaptive energy-mesh scheme for the integration over energy of the density of states and transmission is implemented.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.